2021
DOI: 10.2217/fon-2020-0993
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Lymph Node Ratio as a better Prognostic Tool than The TNM System in Colorectal Cancer

Abstract: Background: The minimum number of lymph nodes that should be evaluated in colon cancer to adequately categorize lymph node status is still controversial. The lymph node ratio (LNR) may be a better prognostic indicator. Materials & methods: We studied 1065 patients treated from 1 January 2000 to 31 August 2012. Results: Significant differences in survival were detected according to regional lymph nodes (pN) (p < 0.001) and LNR (p < 0.001). LRN and pN are independent prognostic factors. Spearman correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…This was also reported by [ 40 , 50 ]. Surprisingly, other potentially significant factors, such as Duke’s stage, tumour stage, tumour grading, tumour location, and tumour histology, which were believed to influence the relationships between response to treatment and survival time of CRC, were not shown by the present study as decisive prognostic factors, and similar results were reported by [ 51 , 52 ]. This was contrary to some pre-existing findings that uphold this former fact [ 30 , 45 , 53 ]; they revealed that, regarding tumour location, patients with CRC located in the colon have a better survival estimate than those with cancer located in the rectum, while CRC patients with an advanced pathological tumour stage, such as stage 4 or Duke D, or poor tumour grade have poor survival outcomes.…”
Section: Discussionsupporting
confidence: 84%
“…This was also reported by [ 40 , 50 ]. Surprisingly, other potentially significant factors, such as Duke’s stage, tumour stage, tumour grading, tumour location, and tumour histology, which were believed to influence the relationships between response to treatment and survival time of CRC, were not shown by the present study as decisive prognostic factors, and similar results were reported by [ 51 , 52 ]. This was contrary to some pre-existing findings that uphold this former fact [ 30 , 45 , 53 ]; they revealed that, regarding tumour location, patients with CRC located in the colon have a better survival estimate than those with cancer located in the rectum, while CRC patients with an advanced pathological tumour stage, such as stage 4 or Duke D, or poor tumour grade have poor survival outcomes.…”
Section: Discussionsupporting
confidence: 84%
“…Zhou et al (10) pointed out that the LNR was an important prognostic factor for non-small-cell lung cancer. Macedo et al (11) indicated that the LNR was a better prognostic tool than the TNM system in colorectal cancer. Our previous study demonstrated that it was an important predictor of poor survival in pancreatic neuroendocrine tumours (12).…”
Section: Introductionmentioning
confidence: 99%
“…Although it had the effect of lowering the survival rate of high-stage patients [ 14 ], it is difficult to predict the prognosis in detail by observing patients with N1b PTC after treatment. To better predict prognosis in patients with N1b PTC, we introduced the concept of LNR, which is known to be a prognostic factor in various types of solid tumors [ 25 , 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%